A genomic case study of mixed fibrolamellar hepatocellular carcinoma. (30th March 2016) - Griffith, O. L.; Griffith, M.; Krysiak, K.; Magrini, V.; Ramu, A.; Skidmore, Z. L.; Kunisaki, J.; Austin, R.; McGrath, S.; Zhang, J.; Demeter, R.; Graves, T.; et al.
Abstract : We report the first comprehensive genomic analysis of a case of mixed conventional and fibrolamellar HCC (mFL-HCC). This study confirms the expression of DNAJB1:PRKACA, a fusion previously associated with pure FL-HCC but not conventional HCC, in mFL-HCC. These results indicate the DNAJB1:PRKACA fusion has diagnostic utility for both pure and mixed FL-HCC. Abstract: Background: Mixed fibrolamellar hepatocellular carcinoma (mFL-HCC) is a rare liver tumor defined by the presence of both pure FL-HCC and conventional HCC components, represents up to 25% of cases of FL-HCC, and has been associated with worse prognosis. Recent genomic characterization of pure FL-HCC identified a highly recurrent transcript fusion ( DNAJB1:PRKACA ) not found in conventional HCC. Patients and Methods: We performed exome and transcriptome sequencing of a case of mFL-HCC. A novel BAC-capture approach was developed to identify a 400 kb deletion as the underlying genomic mechanism for a DNAJB1:PRKACA fusion in this case. A sensitive Nanostring Elements assay was used to screen for this transcript fusion in a second case of mFL-HCC, 112 additional HCC samples and 44 adjacent non-tumor liver samples. Results: We report the first comprehensive genomic analysis of a case of mFL-HCC. No common HCC-associated mutations were identified. The very low mutation rate of this case, large number of mostly single-copy, long-range copy number variants, and high expression of ERBB2 were more consistent with previous reports of pure FL-HCC than conventional HCC. In particular, the DNAJB1:PRKACA fusion transcript specifically associated with pure FL-HCC was detected at very high expression levels. Subsequent analysis revealed the presence of this fusion in all primary and metastatic samples, including those with mixed or conventional HCC pathology. A second case of mFL-HCC confirmed our finding that the fusion was detectable in conventional components. An expanded screen identified a third case of fusion-positive HCC, which upon review, also had both conventional and fibrolamellar features. This screen confirmed the absence of the fusion in all conventional HCC and adjacent non-tumor liver samples. Conclusion: These results indicate that mFL-HCC is similar to pure FL-HCC at the genomic level and the DNAJB1:PRKACA fusion can be used as a diagnostic tool for both pure and mFL-HCC.